Cautery Disbudding Iron Application Time and Brain Injury in Goat Kids: A Pilot Study - Hempstead, Melissa N.; Shearer, Jan K.; Sutherland, Mhairi A.; Fowler, Jennifer L.; Smith, Joseph S.; Smith, Jodi D.; Lindquist, Taylor M.; Plummer, Paul J. (Frontiers in Veterinary Science, 2021)
Cautery disbudding is a painful procedure performed on goat kids to prevent horn growth that may result in brain injury. Thermal damage to the cerebral cortex of the brain and subsequent neurologic disease is a primary concern. Cautery iron application time may affect transmission of heat to the brain; however, research in this area is scarce. Therefore, the objective of this pilot study was to evaluate the effect of iron application time on brain injury of goat kids. A total of six buck and doe kids <9 days of age were obtained from a commercial dairy and transported to an Iowa State University research facility. Kids received a different randomly assigned application time (5, 10, 15, or 20s) on each horn bud. Kids were disbudded using an electric cautery iron (under isoflurane general anesthesia). After a 5-day observation period, the kids were euthanized, and magnetic resonance (MR) images were acquired to evaluate brain injury. Additionally, four of the six kids were presented for gross examination and two kids were selected for histopathologic examination. From the MR images, white matter edema was observed subjacent to four treated areas, representing application times of 5 s (one horn bud), 15 s (one horn bud), and 20 s (two horn buds). With the exception of the horn bud that received 5 s, which had white matter edema restricted to a single gyrus, the remaining three groups had a branching region of edema. No bone abnormalities were identified on any kids. Gross evidence of discoloration and hemorrhage on the cerebral hemispheres was observed on two horn buds that received 20 s, two horn buds that received 15 s, and one horn bud that received 10 s. Microscopic lesions consisting of leptomeningeal and cerebrocortical necrosis were observed in sections of brain from all groups. Lesions were most severe with 20 s. In conclusion, all application times used in this study resulted in some level of brain injury; however, using 15 s or more resulted in more severe and consistent brain injury. These results indicate that extended iron application time may increase the risk of brain injury in cautery disbudded kids.